Development of Nutritional Counseling Materials for ASD Children: Focusing on the Food Exchange List - Seunghyun Won; Youjeong Kim; Jiye Park; Su-in Yoon; Jin Ah Cho (Clinical nutrition research, 2025)
Children with autism spectrum disorder (ASD) often present with selective eating behaviors and dietary imbalances, which contribute to nutritional deficiencies that can adversely impact growth and development. Despite increasing awareness of the role of nutrition in ASD management, existing nutritional interventions frequently fail to accommodate the unique dietary needs of this population. This study aimed to develop tailored nutritional counseling materials for ASD children by adapting the food exchange list framework originally designed for individuals with diabetes. A comprehensive food database was constructed using data from the Korean Diabetes Association, the Korea Rural Development Administration, and related resources, specifically addressing the dietary habits and nutritional deficiencies observed in ASD children. Representative foods were selected, standardized for exchange units, and visually documented through photographs to enhance usability. These elements were integrated into a practical, visually engaging educational brochure, which includes detailed food exchange unit tables, photographic representations of portion sizes, and portion standards to guide caregivers in meal planning. The materials focus on enhancing dietary diversity, correcting common nutrient deficiencies, and fostering balanced eating habits. However, limitations exist in adapting a diabetes-centric framework, which may not fully capture the unique dietary preferences and challenges of ASD children. Nevertheless, the developed materials provide a valuable resource for nutritional education and intervention, supporting the health and development of ASD children. Further research is required to refine these materials and evaluate their effectiveness across diverse settings and populations.